2022
DOI: 10.1039/d1nr06244a
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in flexible and wearable sensors for monitoring chemical molecules

Abstract: In recent years, real-time health management has been received increasing attention, benefiting from the rapid development of flexible and wearable devices. Conventionally, flexible and wearable devices were used in collecting...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 161 publications
0
25
0
Order By: Relevance
“…S4d ), probably caused by a more brittle nature of the laser-induced carbon. Furthermore, it was found that their obtained elasticity is similar to the skin (~ 100 kPa), suggesting the PI nanofiber carring LCNFs are suitable for developing wearable sensors in medical applications [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…S4d ), probably caused by a more brittle nature of the laser-induced carbon. Furthermore, it was found that their obtained elasticity is similar to the skin (~ 100 kPa), suggesting the PI nanofiber carring LCNFs are suitable for developing wearable sensors in medical applications [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Flexible sensors have been attracting great attention due to their potential to be used as wearable chemical sensors [23,24] in the fields of sports [25,26] and health [27], medicine and occupational safety [28]. Hazard identification by monitoring in real-time the body status and the surrounding environment, allows for fast response in order to take countermeasure against potential damage [29][30][31].…”
mentioning
confidence: 99%
“…Specifically, some flexile microfluidic patches fabricated in some studies improved the efficiency of glucose detection in biofluids [ 87 , 88 ]. Furthermore, flexible electronics enables the electrochemical detection circuit that executes electrochemical detection and records detection data to become wearable [ 89 ]. Herein, recent advances towards smartphone-based wearable electrochemical glucose monitoring in sweat, tear, saliva and interstitial fluid were covered and discussed.…”
Section: Smartphone-based Wearable Glucose Monitoringmentioning
confidence: 99%